Beyond degrees: Longer term outcomes of the Kalamazoo Promise - Brad Hershbein; Isabel McMullen; Brian Pittelko; Bridget F. Timmeney (W.E. Upjohn Institute for Employment Research, 2021)
We estimate the effects on workforce and location outcomes of the Kalamazoo Promise, a generous, place-based college scholarship. Drawing upon administrative unemployment insurance wage records merged with individual-level education data, we identify Promise effects by comparing eligible to ineligible graduates before and after the Promise's initiation. We supplement this quantitative analysis with surveys and interviews. Despite earlier research showing that the Kalamazoo Promise substantially increased degree attainment, we find little evidence that the program affected average earnings within 10 years of high school graduation. However, the Kalamazoo Promise may have increased the likelihood of eligible graduates having earnings, within Michigan, in the middle of the distribution. We discuss the possible role of job availability in understanding these patterns and the implications for free-tuition college programs as a workforce development tool.
Keywords: I21; I22; I24; 330; place-based scholarship; difference-in-differences; mixed methods; workforce outcomes; earnings; migration; education policy